The implementation of green tourism in education and research at Bali State Polytechnic - Suardani, Anak Agung Putri; Astawa, I Ketut; Armoni, Ni Luh Eka (Technium Social Sciences Journal, 2023)
The purpose of this research is to analyze the implementation of green tourism in education and research and its implications for the brand image of Bali State Polytechnic. Data collection techniques were observation, interviews, questionnaires, and documentation as well as techniques for determining informants by purposive sampling of 60. The interviews were conducted in a semi-structured manner using an interview guide for key informants to obtain specific information on the research topic. This research was conducted in Bali State Polytechnic and the hospitality industry in Bali. The data analysis technique was carried out using a qualitative descriptive analysis to see the existing conditions of Bali State Polytechnic and then to know the direction of developing Bali State Polytechnic brand image which is oriented towards green tourism. The results of the study show that the implementation of green tourism in education, research, and aspects of forming Bali State Polytechnic brand image show that the average value is in the interval 4.21 - 5.00, meaning that it is in very good category in building brand image of the Bali State Polytechnic. As much as 99% of informants’ perceptions stated that they strongly agreed and agreed regarding the implementation of green tourism in education and research to build a Bali State Polytechnic brand image through the vision and mission. Furthermore, the Bali State Polytechnic through the icon as vocational education produces 98% of graduates who are ready to work. The name of Bali State Polytechnic as a corporate image is easy to remember and 98% believe that the superiority of Bali State Polytechnic’s vocational education model which is oriented towards green tourism will last a long time.